Teachers’ Strategy to Develop Independent Learner Students in EFL Classroom - Raudhatul Jannah; Neni Afrida Sari Harahap; Karunia Devi Frida (Universitas Negeri Medan, 2025)
This study aims to identify teachers’ strategy to develop independent learners and how the teachers implement it in English class. This research uses qualitative descriptive method to describe deeply a phenomenon regarding teacher;s strategy in developing independent learner. The source of this data is 7 teachers in North Sumatera who teach English in Junior High School and Senior High School. The data is all the answers from the teachers through questionnaire. The answer responses are analyzed based on the theories to answer these problems. The results show that the social strategy is the most strategy implement by the teachers and the way they implement by asking students to do collaborative work and asking students to accomplish tasks individually.